Identification of Genes Related to Hair Follicle Cycle Development in Inner Mongolia Cashmere Goat by WGCNA - Gong, Gao; Fan, Yixing; Yan, Xiaochun; Li, Wenze; Yan, Xiaomin; Liu, Hongfu; Zhang, Ludan; Su, Yixing; Zhang, Jiaxin; Jiang, Wei; Liu, Zhihong; Wang, Zhiying; et al. (Frontiers in Veterinary Science, 2022)
Inner Mongolia cashmere goat is an excellent local breed in China, and the related cashmere product is a kind of precious textile raw material with high price. Cashmere is generated from secondary hair follicles, which has obvious annual periodicity and includes three different stages: anagen, catagen and telogen. Therefore, we investigated skin transcriptome data from 12 months using weighted gene co-expression network analysis (WGCNA) to explore essential modules, pathways and genes responsible for periodic growth and development of secondary hair follicles. A total of 17 co-expression modules were discovered by WGCNA, and there is a strong correlation between steelblue module and month (0.65, P=3E-09), anagen (0.52, P=1E-05), telogen (-0.6, P=8E-08). Gene expression was generally high during late anagen to catagen (June to December), while expression was downregulated from telogen to early anagen (January to May), which is similar to the growth rule of hair follicle cycle. KEGG pathway enrichment analyses of the genes of steelblue module indicated that genes are mainly enriched in Cell cycle, Wnt signaling pathway, p53 signaling pathway and other important signal pathways. These genes were also significantly enriched in GO functional annotation of cell cycle, microtubule movement, microtubule binding, tubulin binding and so on. Ten genes (WIF1, WNT11, BAMBI, FZD10, NKD1, LEF1, CCND3, E2F3, CDC6 and CDC25A) were selected from these modules, and further identified as candidate biomarkers to regulate periodic development of hair follicles using qRT-PCR. Wnt signaling pathway and Cell cycle play an important role in the periodic development of hair follicles. Ten genes were identified as essential functional molecules related to periodic development of hair follicle. These findings lay a foundation for understanding molecular mechanisms in biological functions such as hair follicle development and hair growth in cashmere goats.